(untitled) (Journal of Vocational Innovation, Achievement and Education, 2025)
The design of the zero waste-based Integrated Farming System (IFS) model is based on the existing conditions of KWT Nur Rejeki which is still dominated by horticultural cultivation, with an unused 35 m² of land, chicken coops and fish ponds that are not yet functioning optimally, high costs of vegetable production, and the lack of integration of organic waste into productive resources. Objectives. The design of the zero waste-based IFS model as an effort to optimize the use of yard land and increase the income of KWT Nur Rejeki. Methods. A research and development approach with mixed methods is applied through observation, interviews, group discussions, document studies, descriptive analysis, Material Flow Analysis (MFA), waste efficiency, R/C Ratio, Break Even Point (BEP) sales, Margin of Safety (MoS), Payback Period (PP), sensitivity tests, and Likert scale questionnaires with a census study approach through saturated sampling techniques. Results. The design shows the integration of horticulture, laying hens, tilapia, and BSF maggot cultivation in a closed cycle with the potential for organic waste utilization reaching 100% by design. The economic analysis shows that the conservative scenario is feasible to be implemented with an R/C Ratio of 2.18, an estimated net income of Rp705,000 per month, a BEP of Rp118,644, a MoS of 90.91%, and a PP of 2.26 months. The sensitivity test results show that the business is still feasible despite an increase in costs of up to 117.50%, which indicates an increase in economic feasibility compared to existing conditions. The questionnaire results also show that the level of understanding, acceptance, and readiness of members is in the very high category with an average score of 4.58 (91.62%). Conclusion. The zero-waste-based Integrated Farming System model is feasible to be tested through gradual implementation in the Nur Rejeki KWT.